A Study on Teaching Information Literacy Skills to Teachers - Serap Kurbanoğlu; Buket Akkoyunlu (Türk Kütüphaneciliği)
Teaching information literacy skills to the individuals of information society has a great importance. In this paper, necessity of equipping primary and secondary school teachers with information literacy skills is discussed. A study to teach information literacy skills to teachers and the findings of the study will also be introduced.